DENOTATION AND CONNOTATION ON ‘PATHETIC FAIRY TALE BY SAPTARASA - Eka Ugi Sutikno (Universitas Muhammadiyah Tangerang, 2019)
Lyrics of songs are almost similar to poetry, which distinguishes them from song lyrics that do not require deep diction to refer to majas or symbols. Therefore, many song lyrics revolve around the meaning of denotations and connotations. This happened in Saptarasa's Pathetic Fairy Tales song lyrics. This study aims to describe the meaning of denotation and connotation of research data sources, namely Saptarasa's Pathetic Fairy Tales song lyrics. The denotative in this work tells the story of the search for love and also the way of approach. The meaning of the connotation in this work tells us that ‘I’ lyrics cannot reach ‘angel’ and only see it.